PEMBERDAYAAN MASYARAKAT DALAM PUBLIKASI DAN BRANDING DESA WISATA PAAU DI KABUPATEN BANJAR, KALIMANTAN SELATAN - Fahrianoor; M. Najeri Al Syahrin; Aldi Nugroho; Haris Wahyudianor; Adelia; Rinda Nor Hana Alin; Diva Afifah; Muhammad Rizal; Muhammad Faesal Ahsanu; Muslimin; Ervita Amelea (Wadah Inovasi Indonesia, 2022)
Pa'au Village is one of the villages in Aranio District, Banjar Regency, South Kalimantan Province. Paau Village has a lot of tourism potential that can be developed if it is managed properly as a tourist village. However, it is very unfortunate that the lack of tourism development, especially related to existing facilities and infrastructure, has made Pa'au village unable to compete with other regions in South Kalimantan. The limitation of Human Resources in marketing tourism is also one of the obstacles which ultimately results in many outsiders not knowing the existence of Pa'au village. Based on these problems, it is very necessary for us to raise the potential of the tourism village through socialization of publications to social media, the main purpose of this activity is that the village community will be able to play an active role, have skills and have awareness to develop the potential of the Pa'au tourist village.